Understanding nano-impacts: impact times and near-wall hindered diffusion - Katelhon, E; Compton, R (2014)
© the Partner Organisations 2014. We report the residence time of freely-diffusing, catalytically-active nanoparticles within a electron tunnelling distance of a surface. The role of near-wall hindered diffusion is paramount and leads to the new concept of "hydrodynamic adsorption". We give a comprehensive statistical analysis of the average impact times and derive expressions for a number values, crucial for the analysis of experimental data. Random walk simulations confirm the distribution of impact times with broad implications for nanochemistry.